Environmental Exploitation in Chandra Bientang's Novel Batu Berkaki: An Ecocritical Study - Witrian Harun; Sitti Rachmi Masie; Zilfa Achmad Bagtayan (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
Chandra Bientang’s novel Batu Berkaki (2024) depicts society’s struggle to deal with environmental damage triggered by human greed and efforts to restore the balance of nature through moral values and ecological awareness. This study examines the representation of environmental exploitation and environmental ethics in the novel. Specifically, the study aims to (1) describe forms of environmental exploitation based on Garrard’s perspective, and (2) describe forms of environmental ethics based on Keraf’s perspective. The study uses Garrard’s ecocritical theory as a basis for examining the relationship between humans and nature in literary works, and Keraf’s environmental ethical theory to explain the moral values that guide humans in preserving the environment. The method used is descriptive qualitative. The research data consists of excerpts from the novel Batu Berkaki that depict acts of exploitation and ethical behavior towards the environment. Data sources come from the main novel and are supported by relevant theoretical references. Data collection techniques are carried out through reading and note-taking, while data analysis includes systematic reduction, classification, description, and drawing conclusions. The results of the study showed 42 data representing environmental exploitation, consisting of pollution (11 data), wilderness (8 data), natural disasters (1 data), residence (11 data), animals (7 data), and the earth (4 data). In addition, 19 data were found related to environmental ethics which include respect for nature, responsibility, solidarity, compassion, the principle of no harm, a simple and harmonious life towards nature, the principle of justice, the principle of democracy, and the principle of moral integrity. These findings confirm that the novel Batu Berkaki not only highlights ecological damage, but also offers moral values as a foundation for sustainable environmental recovery and supports the interests of the ecosystem.